Design of Partially Suspended Silicon Nitride Slot Waveguides for Efficient Forward Stimulated Brillouin Scattering - Kang Wang; Junqiang Sun; Ming Cheng (IEEE Photonics Journal)
We design a partially suspended silicon nitride (Si3N4) slot waveguide on silica to realize efficient on-chip forward stimulated Brillouin scattering (FSBS). The slot waveguide can intensify radiation pressure close to the slot and simultaneously confine both optical and acoustic modes, resulting in an enhanced FSBS gain on the order of 300 W−1m−1. The acoustic radiation loss is significantly suppressed due to the strong acoustic coupling in the narrow slot waveguides. We analyze the impacts of structural parameters on the SBS properties, which produces the optimal parameters for maximum SBS gain. Based on the nonlinear coupled-mode equations, we compare the performance of Stokes amplification between the Si3N4 slot waveguides and the silicon nanowires. Simulation results indicate that the Si3N4 slot waveguides with low linear loss can offer a larger net Stokes amplification than silicon waveguides under moderate pump power. Such approach enables efficient on-chip SBS devices in CMOS-compatible Si3N4 platform.